2007
DOI: 10.1017/s1047951107000674
|View full text |Cite
|
Sign up to set email alerts
|

Left-sided aortic arch, right-sided descending aorta, and right-sided arterial duct associated with interruption of the aortic arch and presence of Abbott’s artery

Abstract: We describe a male infant, seen at the age of 10 days, with a very rare form of vascular ring. The aortic arch was left-sided, but the aorta descended on the right, with a right-sided persistently patent arterial duct associated with interruption of the aortic arch and presence of Abbott's artery. We performed end-to-side anastomosis of the descending aorta to the ascending aorta, divided the Abbott's artery and the right-sided arterial duct, and banded the pulmonary trunk. Despite our best efforts, the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…When arch hypoplasia is present, it can be tubular with a long segment, or tortuous, extending from the proximal to distal transverse arch as it courses around the side of the trachea and back of the oesophagus [5][6][7]28] . A long hypoplastic retroesophageal segment can be mistaken as an Abbott artery which is an anomalous artery arising from the posterior wall of the aortic arch or others in coarctation of the aorta [30][31][32] .…”
Section: Concomitant Lesionsmentioning
confidence: 99%
“…When arch hypoplasia is present, it can be tubular with a long segment, or tortuous, extending from the proximal to distal transverse arch as it courses around the side of the trachea and back of the oesophagus [5][6][7]28] . A long hypoplastic retroesophageal segment can be mistaken as an Abbott artery which is an anomalous artery arising from the posterior wall of the aortic arch or others in coarctation of the aorta [30][31][32] .…”
Section: Concomitant Lesionsmentioning
confidence: 99%
“…The association of VR with IAA is extremely rare [2,3]. McElhinney and colleagues [4] reported that chromosome 22q11 deletion is associated with isolated anomalies of aortic arch laterality and branching.…”
Section: Commentmentioning
confidence: 99%